(untitled) (Proximus Journal of Sports Science and Physical Education, 2026)
In recent years, the development of young athletes in track and field has become a central focus of sports science, particularly in the context of optimizing training processes and enhancing performance outcomes. Modern athletics requires not only high physical preparedness but also the implementation of scientifically grounded training methodologies that take into account the individual characteristics of athletes. In this regard, individualized training programs are increasingly recognized as a key factor in improving athletic performance and ensuring long-term athlete development. The relevance of this study is обусловлена the growing need to design training systems that correspond to the biological, physiological, and psychological особенностям young athletes. Traditional “one-size-fits-all” training approaches often fail to consider significant inter-individual differences in growth, maturation, and adaptation to нагрузка, which can lead to suboptimal performance outcomes and increased risk of injury. Contemporary research emphasizes that youth athletes exhibit substantial variability in developmental trajectories, and therefore require tailored training interventions aligned with their individual capacities and needs